BUSINESS STRATEGY ASSISTANCE AND TRAINING FOR MICRO, SMALL, AND MEDIUM ENTERPRISES - Saut Maruli Tua Pandiangan; Siti Annisa Wahdiniawati; Ratih Pratiwi; Balla Wahyu Budiarto; Ilham Arief (Bajang Institute, 2023)
The purpose of this community service activity is to socialize business strategy assistance and training for micro, small, and medium enterprises. Based on the problems found and formulated, the problem-solving framework carried out through this community service activity is to socialize digital marketing business strategies in order to help increase sales to micro, small, and medium enterprises. The implementation of this community service activity is carried out using lecture, tutorial, and discussion methods. This socialization activity is very beneficial for micro, small, and medium enterprises who have businesses. Through this outreach activity, it is hoped that it can increase awareness of micro, small, and medium enterprises actors in East Medan District, Medan City, North Sumatra Province to start practicing using Facebook or Instagram for product promotion.